2016
DOI: 10.1002/cmdc.201600248
|View full text |Cite|
|
Sign up to set email alerts
|

Substrate Fragmentation for the Design of M. tuberculosis CYP121 Inhibitors

Abstract: The cyclo‐dipeptide substrates of the essential M. tuberculosis (Mtb) enzyme CYP121 were deconstructed into their component fragments and screened against the enzyme. A number of hits were identified, one of which exhibited an unexpected inhibitor‐like binding mode. The inhibitory pharmacophore was elucidated, and fragment binding affinity was rapidly improved by synthetic elaboration guided by the structures of CYP121 substrates. The resulting inhibitors have low micromolar affinity, good predicted physicoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 49 publications
(123 reference statements)
0
14
0
Order By: Relevance
“…[11,15] Kavanagh et al designed compounds based on substrate fragmentation with micromolar affinity and selectivity over other Mtb P450'sw ithout data concerning biological activity. [16] Regarding compounds with cellular activity, it was shown that azole antifungals bind tightlyt oCYP121and exhibit an in vitro and in vivo activity against Mtb. [17][18][19][20][21][22] Furthermore, the bindingt ot he enzyme was in good correlation with the antimycobacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…[11,15] Kavanagh et al designed compounds based on substrate fragmentation with micromolar affinity and selectivity over other Mtb P450'sw ithout data concerning biological activity. [16] Regarding compounds with cellular activity, it was shown that azole antifungals bind tightlyt oCYP121and exhibit an in vitro and in vivo activity against Mtb. [17][18][19][20][21][22] Furthermore, the bindingt ot he enzyme was in good correlation with the antimycobacterial effect.…”
Section: Introductionmentioning
confidence: 99%
“…The ester ( S )‐ 3 was accessible through the Steglich esterification . We synthesized the bioisostere ( S )‐ 4 from the building blocks thioamide ( S )‐ 7 and ketobromide 9 , which can be both accessed in two steps from N ‐α‐Boc‐ l ‐tryptophan ( 5 ) and mesitylacetic acid ( 8 ), respectively.…”
Section: Figurementioning
confidence: 99%
“…As part of continuing efforts aimed at the discovery of novel inhibitors of CYP121A1 [ [8] , [9] , [10] ], the binding mode of a novel class of inhibitors with moderate activity against Mtb strain H37Rv was reinvestigated. Previous work had shown that a series of d -tryptophan derived thiazoles exhibited moderate potency ( K d ∼ 30–55 μM) against CYP121A1 in a UV–Vis spectrophotometric assay [ 10 ]. Some members of the series ( Fig.…”
Section: Introductionmentioning
confidence: 99%